KELIMPAHAN, DISTRIBUSI, DAN KERAGAMANNUDIBRANCHIA DI NUDIFALL DAN NUDIRETREAT SELAT LEMBEH, SULAWESI UTARA - Pricilia OM Ompi; Farnis B Boneka; Medy Ompi; Joice S Rimper; Kakaskasen A Roeroe; Alex D Kambey (Sam Ratulangi University, 2019)
Nudibranchia are known as marine invertebrates that have uniq colors and body shapes. The research was conducted in Nudifall and Nudiretreat, Lembeh Strait, North Sulawesi. The aims of this study were 1) to identify the species of Nudibranchia in both locations, 2) to know the abundance of Nudibranchia in those locations, 3) to determine distribution patterns of nudibranchia, and to know diversity of Nudibranchia in both Nudifall and Nudiretreat. The results show that 11 species of Nudibranchia were found in both Nudifall and Nudiretreat. The species of Chromodoris annae, Chromodoris magnifica, Flabellina expotata, Goniobranchus fidelis, Halgerda batangas, and 1 unidentified species were found in Nudifall, while the species of Goniobranchus geometricus, Glossidoris cincta, Phylllidia ocelata, Phylllidia varicose, Nembrotha rutilans were found in Nudiretreat. H. batangas was found to be the highest abundance, then it was followed byC. annae, C. magnifica, G. fidelis, unidenfied species (species-1), and C. magnificain Nudifall. P. ocelatawas found to be the highest abundance, then it was followed by G. geometricus, G. cincta, P. varicose, andN. Rutilans in Nudiretreat. Nudibranchia in both locations wasidentified to have random and grouped distribution pattern. Nudibranchia was found to have the same diversity among Nudifall and Nudiretreat. Factors affecting abudance, distribution patterns, and diversity were discuss in this paper.Keywords: Nudibranchia, Distribution, Abudance, Lembeh Strait. Nudibranchia dikenal sebagai avertebrata laut yang memiliki warna unik dan bentuk tubuh yang bervariasi. Penelitian ini di lakukan di Nudifall dan Nudiretreat, Selat Lembeh, Sulawesi Utara. Tujuan penelitian ini adalah 1) mengidentifikasi jenis-jenis nudibranchia di lokasi Nudifall dan Nudiretreat, 2) mengetahui kelimpahan jenis-jenis Nudibranchia di kedua lokasi, 3) mengetahui pola distribusi jenis-jenis Nudibranchia di lokasi Nudifall dan Nudiretreatdi, 4) dan keragaman Nudibranchia di Nudifall dan Nudiretreat. Ada 11 jenis Nudibranchia ditemukan di kedu lokasi penelitian.Nudibranchia yang ditemukan di Nudifall ada 6 jenis, yaitu Chromodoris annae, Chromodoris magnifica, Flabellina expotata, Goniobranchus fidelis, Halgerda batangas, dan 1 spesies belum teridentifikasi (spesies-1). Nudibranchia yang ditemukan di Nudiretreat ada 5 jenis,yaitu Goniobranchus geometricus, Glossidoris cincta, Phylllidia ocelata, Phylllidia varicose, Nembrotha rutilans. H. batangas memiliki kelimpahan yang tinggi, kemudian diikuti oleh C. annae, C. magnifica, G.fidelis, spesies-1, dan C. magnifica.di Nudifall.P. ocelata memiliki rata-rata tertinggi, selanjutnya diikuti oleh G. geometricus, G. cincta, P. varicose, dan N. Rutilans di Nudiretreat.Pola sebaran acak dan berkelompok teridentifikasi pada kedua lokasi.udibranchia teridentifikasi memiliki keragaman yang sama di kedua lokasi. Faktor-faktor yang mempengaruhi kelimpahan, distribusi, dan keragaman didiskusikan pada tulisan ini.Kata kunci: Nudibranchia, Distribusi, Kelimpahan, Selat Lembeh.